Factor Association Related to Husband's Support Behavior in the Cervical Cancer Prevention Based on Theory of Planned Behavior - Permata Sari, Aprilia (International Journal of Psychosocial Rehabilitation, 2020)
Husband's support is an important interpersonal factor in the cervical cancer prevention performed by women; however, there are still many women who are reluctant to do this early detection, so it needs understanding related to the factor of husband's support behavior to maximize the prevention effort of cervical cancer. This study aims to analyze the factors related to husband's support behavior in cervical cancer prevention based on the Theory of Planned Behavior. This study used a descriptive analytic with a cross-sectional design. The samples were 102 husbands who were childbearing couples taken using the cluster sampling technique. The variables of this study were the husband's attitude, the husband's subjective norm, the husband's perceived behavioral control, the husband's intention, and the husband's support behavior in cervical cancer prevention. The data analysis was performed using Spearman's Rho with a significance level of ≤ 0.05. The result showed a significant relationship between attitude with intention (p = 0,000; r = 0,377), perceived behavioral control with intention (p = 0,003; r = 0,289), and intention with husband's support behavior in cervical cancer prevention (p = 0,000; r = 0.431). Subjective norm with intention indicates an insignificant relationship (p = 0.059; r = 0.188). The positive attitude and perception of behavioral control in the Theory of Planned Behavior affect the support of the husband, who encourages high intention so that it has implications for the creation of the husband's support behavior in the prevention of cervical cancer.